Effects of heavy metal accumulation on biological activities and genetic variation of Centella asiatica ( L.) urban - Ong, Ghim Hock (2012)
Trace metals have become a main concern nowadays because these metals may be transferred and accumulated in the body of animals or human beings through the food chain. Trace metals are toxic to the biota at high bioavailabilities, hence trace metal contamination in medicinal plants should be monitored to ensure the safety of consumers. Centella asiatica is sedentary, abundant, easily to be identified, large enough for analysis, has the potential to reflect bioavailability and tolerant to the raised of metal bioavailability in the environment. Hence, it is suitable to be used as a biomonitor. The first objective was to determine trace metals accumulation of C. asiatica collected from 16 sampling sites from Peninsular Malaysia. The metals determined included As, Al, Cd, Co, Cr, Zn, Ba, Br, Ca, Ce, Cs, Cu, Dy, Eu, Fe, Ga, Hf, K, La, Lu, Mg, Mn, Na, Ni, Pb, Rb, Sc, Sm, Ta, Tb, Th, Ti, U, V, Yb, Zn, Zr by air-acetylene flame Atomic Absorption Spectrophotometer (AAS) and Instrument Neutron Activation Analysis (INAA). The second objective was to determine the relationship between metal accumulations and antioxidative activities in C. asiatica from 16 sampling sites from Peninsular Malaysia. The third objective was to determine the tolerance and toxicities of Pb, Cu and Zn to C. asiatica and their metal effects to the antioxidative levels under laboratory conditions. The fourth objective was to assess the accumulation of trace metals by using transplanted C. asiatica between control and semi-polluted or polluted sites. Lastly, the objective was to determine the relationships between genetic variations and metal concentrations based on polluted and clean populations of C. asiatica from the transplantation study. According to the results, the metal accumulations were highest in roots followed by leaves and stems. This study revealed positive and significant correlations (P<0.05) between plant (leaves, stems and roots) and soil for such as Ba, Br, Ca, Ce, Cs, Ga,Hf, K, La, Mg, Mn, Na, Rb, Sb, Ta, Th, U, V, Yb, Zn and Zr. It was found that only a few metals showed significant correlation between metals and antioxidative enzymes in leaves of C. asiatica including Ca, Cd, Ce, Cu, Hf, K, La, Mg, Mn, Ni, Pb, Rb, Ta and Zn. For the toxicity studies, the leaves, stems and roots were significantly correlated with one another for Cu, Pb and Zn. It was found that Zn correlated significantly with all antioxidative enzymes in leaves. Pb was correlated significantly with Catalases (CAT) but Cu did not show any correlation with antioxidative enzymes in leaves. In roots, Zn showed significant correlations with Guaiacol peroxidise (GPX) and Ascorbate peroxidise (APX) while Cu showed significant correlations with Superoxide dismutase (SOD) and GPX. For the transplantation study, the accumulation of metals increased for all parts when transplanted from control to semi-polluted or polluted sites under field conditions (week 0 to week 3). However, the accumulation decreased (week 3 to week 6) after transplantation from the semi-polluted and polluted sites back to the control sites. Higher levels of metals were found in the back-transplanted plant in week 6 than in week 0 in that they were far from reaching the initial metals concentration (week 0). The findings of the present study indicated that the leaves, stems and roots of C. asiatica are good biomonitors of trace metal ontaminations. For the transplantation study under field and laboratory conditions, the dendrogram divided the populations into two major groups. UPM week 3 and UPM week 6 were grouped in a major cluster, whereas Juru week 3, Juru week 6, Balakong week 3, Balakong week 6, SK week 3 and SK week 6 were grouped in another major cluster. From the present results, it was found that correlations of metal accumulations between C. asiatica and genetic variations occurred. The findings of the present study indicated that the leaves, stems and roots of C. asiatica are good biomonitors of metal contaminations. The present data are the results of the most comprehensive study done on terrestrial metal levels in Malaysia.